(untitled) - Gruber, Harald (Cambridge, UK, 2005)
The mobile telecommunications industry is one of the most rapidly growing sectors around the world. This book offers a comprehensive economic analysis of the main determinants of growth in the industry. Harald Gruber demonstrates the importance of competitive entry and the setting of technological standards, both of which play a central role in their contribution to the fast diffusion of technology. Detailed country studies provide empirical evidence for the development of the main themes: the diffusion of mobile telecommunications services, the pricing policies in network industries, the role of entry barriers such as radio spectrum and spectrum allocation procedures. This research-based survey will appeal to a wide range of applied industrial economists within universities, government and the industry itself.
Keywords: Cellular telephone services industry,Mobile communication systems,Wireless communication systems; Economic aspects,Economic aspects